Erythronium japonicum Alleviates Inflammatory Pain by Inhibiting MAPK Activation and by Suppressing NF-κB Activation via ERK/Nrf2/HO-1 Signaling Pathway - Joon Park; Yun Tai Kim (Antioxidants, 2020)
Microglial activation-mediated neuroinflammation influences the development of inflammatory pain. The aim of this study was to investigate the anti-inflammatory effects and mechanisms of aqueous Erythronium japonicum extract (EJE) in microglia activation-mediated inflammatory pain. EJE was found to suppress lipopolysaccharide (LPS)-induced inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), ionized calcium-binding adapter molecule 1 (IBA-1), and pro-inflammatory cytokines in BV2 microglial cells. In addition, LPS-induced c-Jun NH2 terminal protein kinase (JNK) and p38 mitogen-activated protein kinase (MAPK) phosphorylation were inhibited by EJE. Intriguingly, EJE also inhibited p65 phosphorylation by activating extracellular signal-regulated kinase-1/2 (ERK)/nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling. Furthermore, the effects of EJE treatment, such as HO-1 induction and the reduction of NF-ĸB activation, were reversed by ERK1/2 inhibition. In an inflammatory pain mouse model, Complete Freund’s Adjuvant (CFA)-induced mechanical allodynia and foot swelling were alleviated by the oral administration of EJE. Consistent with in vitro results, EJE increased HO-1, while decreasing CFA-induced COX-2, IBA-1, and pro-inflammatory cytokines in the spinal cord. Among the components of EJE, butanol most heavily suppressed LPS-induced microglial activation and increased HO-1 expression. These findings indicate that EJE can alleviate inflammatory pain by inhibiting p38 and JNK and by suppressing NF-ĸB via ERK/Nrf2/HO-1 signaling.